2002
DOI: 10.1034/j.1600-0773.2002.900304.x
|View full text |Cite
|
Sign up to set email alerts
|

Altered Pharmacokinetics and Metabolism of Valproate after Replacement of Conventional Valproate with the Slow‐Release Formulation in Epileptic Patients

Abstract: Altered metabolism of valproate has been suggested as the mechanism of teratogenicity and hepatotoxicity of valproate. This study aimed at examining whether pharmacokinetics of a slow-release formulation of valproate affects valproate metabolism. Thirty-one epileptic patients were treated with fixed-doses of conventional valproate for at least 2 months. Thereafter, the drug was replaced with the same doses of slow-release formulation of valproate for 2 months. Blood samplings for determination of valproate and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 16 publications
(26 reference statements)
1
11
0
Order By: Relevance
“…Although we chose a different approach to this topic, our findings are in concordance with previous research (5,10,11). For example, Doughty et al (11) reported data about compliance and satisfaction in epilepsy patients who changed from sodium VPA to a controlled-release formulation.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Although we chose a different approach to this topic, our findings are in concordance with previous research (5,10,11). For example, Doughty et al (11) reported data about compliance and satisfaction in epilepsy patients who changed from sodium VPA to a controlled-release formulation.…”
Section: Discussionsupporting
confidence: 87%
“…The characteristic kinetic profiles of controlled-release VPA as compared with those of conventional VPA were delayed peak time and reduced peak concentration. In addition, Kondo et al (5) showed that the controlled-release VPA formulation causes smaller diurnal fluctuations in serum concentration than does VPA. The smaller fluctuations result in decreased formation of toxic metabolites, which could be of relevance for adverse effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…), mechanism for MR, extent of bioavailability (%), requirement for total daily mg dose adjustment for the MR AED vs. the IR formulation, duration of C min maintenance (h), T max (h) for both single dose and steady-state conditions, longest FDA ⁄ European Medicines Agency-approved dosing frequency (h), absorption (52) have been approved for use in the USA for some time; some generic DVPX formulations, both enteric-coated and ER, have recently become available, but these generic formulations are not included in our analysis because of the relative inaccessibility of the pharmacokinetic and formulation data concerning these products. Multiple forms of enteric-coated NaVPA exist worldwide, and several sustained-release (SR) VPA ⁄ NaVPA forms exist worldwide [Japan (53,54); Germany (55)], but only the most broadlyrecognized branded formulations (-Chrono Ò and -Chronosphere Ò ; Sanofi-Aventis, Paris, France) are included here so that the huge class of VPA ⁄ NaVPA formulations available would not dominate the information presented here.…”
Section: Methods Smentioning
confidence: 99%
“…• There is some evidence that extended-release preparations may be safer in pregancy. 23 • Take total and free levels (if available) of the drug monthly at trough times.…”
Section: Tablementioning
confidence: 99%